Clutter Cancellation Along the Clutter Ridge for Airborne Passive Radar - Yang, Peng-Cheng; Lyu, Xiao-De; Chai, Zhi-Hai; Zhang, Dan; Yue, Qi; Yang, Jing-Mao (IEEE geoscience and remote sensing letters, 2017)
This letter examines the problem of clutter cancellation in airborne passive radar. This problem is exacerbated by the Doppler spread of clutter due to the receiver motion, since targets falling in the clutter Doppler band will be canceled. To address this problem, a least mean square-based algorithm is proposed for the sidelooking airborne passive radar. Making use of the directional dependence of the clutter Doppler frequency, this algorithm cancels clutter along the clutter ridge and thus avoids the cancellation of targets. Simulations with the experimental data show that clutter can be canceled ideally with the proposed algorithm and signal-to-noise ratio losses are slight, for example, the losses are within 1 dB for targets with radial velocity greater than 10 m/s.